Q. 763.7( 3 Votes )

# Solve the following question.

4 (3p + 2) – 5(6p – 1) = 2 (p – 8) – 6 (7p – 4)

Answer :

Given equation is,

⇒ 4(3p + 2)-5(6p-1) = 2(p-8)-6(7p-4)

⇒ 12p + 8-30p + 5 = 2p-16-42p + 24

⇒ -18p + 13 = -40p + 8

⇒ -18p + 40p = 8-13 (transposing – 40p to LHS and 13 to RHS)

⇒ 22p = -5

⇒ Hence value of p is .

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Linear Equation in One Variable46 mins

Champ Quiz | Linear Equation in One Variable44 mins

Quiz | Linear Equation in One Variable48 mins

Genius Quiz | Solutions of Linear equation in One Variable26 mins

Quiz | Imp. Qs. on Linear Equation in One Variable34 mins

Champ Quiz | Trail of Questions on Transposition Method51 mins

NCERT | Imp. Question Discussion on Linear Equation in One Variable43 mins

NCERT - Imp. Qs. Discussion From Linear Equation in One Variable45 mins

Making Equations Simple41 mins

NCERT | Imp. Questions on Solutions of Linear Equations in One Variable39 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

if , then x = ?

RS Aggarwal - MathematicsSolve each of the following equations and also check your result in each case:

RD Sharma - Mathematics

If, then n = ?

RS Aggarwal - MathematicsIf then x = ?

RS Aggarwal - MathematicsIf then x = ?

RS Aggarwal - Mathematics